Re-structuring library resources and services in IIT Delhi library: analytical study from users' perspective. (10th June 2021) - Kumar, Rajender; Gupta, Dinesh K.
Abstract : Purpose: This study aims to assess users' satisfaction from the re-structured library resources and services due to technological innovations in the Indian Institute of Technology Delhi library. It also identifies and suggests potential improvement areas. Design/methodology/approach: The study adopts a survey research method to collect data from the end-users of the library. Data were collected through a structured questionnaire. In total, 100 copies of questionnaires were distributed to the students, and out of the filled received questionnaires, 92 were found dully completed and useable. Collected data were analyzed by using percentage and chi-square test for testing of hypothesis. Findings: This study shows that users' usage and preference for e-resources and e-services are increasing as there is a general trend to overlook traditional print resources where e-resources are available in the first place. The study recommends that a radical rethinking is required to strengthen the electronic collection and improve the library services. Practical implications: The paper has a direct practical implication. It suggests that as technology continues to evolve, it is likely that academic institutes find themselves identifying appropriate areas to redesign library activities and services regularly. This paper reveals the practice of re-engineering in academic library services and knowing students' specific preferences of resources and services to enhance library usage. Originality/value: The study is based on the self-designed structured questionnaire. Primary data has been collected from the IIT Delhi library users, thus providing original information and informative inputs to the existing literature.